Activation of Host IRE1α-Dependent Signaling Axis Contributes the Intracellular Parasitism of Brucella melitensis - Pandey, Aseem; Lin, Furong; Cabello, Ana L.; da Costa, Luciana F.; Feng, Xuehuan; Feng, Hui-Qiang; Zhang, Ming-Zhe; Iwawaki, Takao; Rice-Ficht, Allison; Ficht, Thomas A.; de Figueiredo, Paul; Qin, Qing-Ming (Frontiers in Cellular and Infection Microbiology, 2018)
Brucella spp. are intracellular vacuolar pathogens that causes brucellosis, a worldwide zoonosis of profound importance. We previously demonstrated that the activity of host unfolded protein response (UPR) sensor IRE1α (inositol-requiring enzyme 1) and ER-associated autophagy confer susceptibility to B. melitensis and B. abortus intracellular replication. However, the mechanism by which host IRE1α regulates the pathogen intracellular lifestyle remains elusive. In this study, by employing a diverse array of molecular approaches, including biochemical analyses, fluorescence microscopy imaging, and infection assays using primary cells derived from Ern1 (encoding IRE1) conditional knockout mice, we address this gap in our understanding by demonstrating that a novel IRE1α to ULK1, an important component for autophagy initiation, signaling axis confers susceptibility to Brucella intracellular parasitism. Importantly, deletion or inactivation of key signaling components along this axis, including IRE1α, BAK/BAX, ASK1, and JNK as well as components of the host autophagy system ULK1, Atg9a and Beclin 1, resulted in striking disruption of Brucella intracellular trafficking and replication. Host kinases in the IRE1α-ULK1 axis, including IRE1α, ASK1, JNK1 and/or AMPKα as well as ULK1, were also coordinately phosphorylated in an IRE1α-dependent fashion upon the pathogen infection. Taken together, our findings demonstrate that the IRE1α-ULK1 signaling axis is subverted by the bacterium to promote intracellular parasitism, and provide new insight into our understanding of the molecular mechanisms of intracellular lifestyle of Brucella.